PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING ( STUDI KASUS PADA KARYAWAN PT. INTINUSA SELAREKSA,TBK) - Ryan Syahgani; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2017)
The fairly tight business competition at the global level will lead to rapid environmental change, characterized by the advancement of information, the variety of high demand, the demographic changes and economic fluctuations. That tight business requires the personnel in the organization to have a better performance.In the relation of human resources, the changes organizational environment, both internal and external, directly or indirectly, might affect employees’ work motivation and organizational climate that can increasing or reducing the level of job satisfaction that evoke employees’ intention to move from their recent jobs (turnover inention) and it could evoke the actual turnover. In PT. Intinusa Selareksa,Tbk., there is an indication in decreasing of the level of job satisfaction, that can lead to employees’ turnover intention.The purpose of this research is to find out the effect of work motivation and organizational climate toward employees’ turnover intention through job satisfaction at PT. Intinusa Selareksa,Tbk. The type of this research is explanatory research, with interviews and questionnaires as data collection technique. The sampling method using proportionate random sampling with 105 employees of PT. Intinusa Selareksa,Tbk. as the participants. The data analysis conducted quantitatively with SPSS version 20.The result of the research indicates that work motivation and organizational climate have positive effect to job satisfaction, and the job satisfaction has negative effect to turnover intention. The organizational climate has the dominant influence, that indicated from primary data analysis using test validity, test reliability, coefficient of correlation, linear regression, coefficient of determination, t-test and two pass regression. The result of this study tells us that the company should improving and keeping good work environment in order to better employees’ performances, that will lead to the increase of job satisfaction, and reducing the turnover intention.